Genres apart : School and University writing - Ting, Su Hie; Muriatul Khusmah, Musa (Issues in Language Studies, 2013)
This study examined the types of writing emphasised in secondary school and university. The specific aspects studied were the genres that students write best, genres frequently written in school, and genres frequently required in written coursework assignments in university. The data on school writing were obtained from questionnaires distributed to 235 students enrolled in English courses in two Malaysian universities whereas the data on university coursework assignments were obtained through interviews with lecturers in the two universities. The results showed that there is a mismatch between types of writing emphasised in school and university. Students frequently write recount and discussion in school but university coursework frequently requires assignments to be written in the form of research articles and explanations. In view of the different emphases in school and university writing, students entering university have difficulty coping with academic discourse. The findings suggest that it is beneficial to sensitise university students to textual conventions of commonly used academic genres at university to speed up their learning of academic discourse.